Perancangan Dan Analisis Performansi Private Cloud Computing Untuk Penyimpanan Data Di SMPN 1 Karimun - Muhammad Ridwan Saputra; Ery Safrianti; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The development of information technology has ampact on changes in human life. One of them is Cloud Computing technology. Cloud Computing is computing model that it giveaway saat toaccess services by offering resources suci as hardware, software, and data storage as user guidance services. SMPN 1 Karimun is one of the Junior High Schools in Karimun Regency,still uses conventional storage namely computer storage or tiger storages. So, the ampun of data cause a lack of effeciency and effectiveness in accessing data. As a technology like cloudcomputing. Cloud computing has function as a server for digital-based storage, renew using cloud computing can storage performance in SMPN 1 Karimun to knot it any attack of DoS ( Denial of Service ). The research methodology is to design a cloud computing system by testings function in the application with the quality of existing network. The average value of throughput without DoS attack is 21,21 Mbit/s, the average throughtput value two PCs using DoS attack is18,76 Mbit/s while four PCs is 17,21 Mbit/s. Avarage result of packet loss without DoS attack is 0,046 %, the average of packet loss value using two PCs DoS attack is 0,082 % while using fourPCs is 0,104 %. Average result of delay value without DoS attack is 0,000354 ms, the average delay value using two PCs is 0,000475 ms while using while four PCs is 0,000517 ms.Keywords: Cloud Computing, DoS (Denial of Service), QoS (Quality of Service), SMPN 1 Karimun